The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/jhass-07-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, care-seeking behaviors and treatment cost for neonatal morbidities in Karnataka (India)

Abstract: Purpose Around three million infants die within the first four weeks of life each year – nearly all (98%) of these deaths occur in developing countries. Approximately one million newborns die each year in India. Therefore, this study aims to determine the patterns of reported neonatal morbidity and care-seeking behavior and identify factors associated with it. Design/methodology/approach A cross-sectional study was conducted during November 2016. A systematic random sampling technique was used to select the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Consequently, performing jaundice diagnosis away from the hospital is nearly impossible. In most newborns, the bilirubin content peaks within a few days after discharge from the hospital [5,6]; therefore, visual observation of neonatal jaundice symptoms by parents is the most common detection method. However, research has suggested that even the most experienced physicians cannot accurately identify neonatal jaundice using unaided vision [7].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, performing jaundice diagnosis away from the hospital is nearly impossible. In most newborns, the bilirubin content peaks within a few days after discharge from the hospital [5,6]; therefore, visual observation of neonatal jaundice symptoms by parents is the most common detection method. However, research has suggested that even the most experienced physicians cannot accurately identify neonatal jaundice using unaided vision [7].…”
Section: Introductionmentioning
confidence: 99%